NILAI PENDIDIKAN KARAKTER PADA NASKAH DRAMA DALAM BUKU TEKS BAHASA INDONESIA KELAS XI SMA: THE VALUE OF CHARACTER EDUCATION IN DRAMA SCRIPTS IN INDONESIAN LANGUAGE TEXTBOOKS CLASS XI SMA - Nirwana; Saleh, Muhammad; Azis (Journal of Applied Linguistics and Literature, 2025)
This research aims to describe the form and function of character education values in drama scripts. This research uses a descriptive qualitative approach, the source of data from the drama script. The form of data is in the form of phrases, sentences, and quotations in drama scripts in Indonesian language textbooks. Data collection techniques are note-taking and reading techniques. Data analysis techniques in this study used Miles and Huberman data analysis, namely data collection, data reduction, data presentation, and conclusion drawing. The results showed that the form of character education values in drama texts in Indonesian textbooks are religious character education values, nationalism, integrity, independence, and mutual cooperation. The function of character education values found in drama texts in Indonesian language textbooks is to develop the character of students to become human beings who have faith and devotion to God Almighty, have noble character, have democratic principles, develop positive attitudes, strengthen and develop ethical and moral values, develop a sense of leadership, improve the quality of life, have knowledge, and overcome challenges and difficulties.